Leaner Women with Impaired Insulin Secretion Accounts for about 40% of Gestational Diabetes Mellitus in Japan - Seishi Furukawa; Yoichi Kobayashi (Journal of Pregnancy)
Aim. To identify the involvement of leanness and impaired insulin secretion with Japanese gestational diabetes mellitus (GDM). Method. A cross-sectional study was conducted comprising 219 at-risk pregnant women who underwent a 75g glucose tolerance test at a single institute in Tokyo, Japan. We identified GDM and normal glucose tolerance (NGT). The cut-off value of the homeostasis model assessment insulin resistance (HOMA-IR) for detecting GDM was determined. The GDM group was divided into subgroups according to insulin resistance based on the cut-off value of HOMA-IR. We compared the prepregnancy body mass index (BMI) and homeostasis model assessment of β-cell function (HOMA-β) between the group comprising low insulin resistance (LIR) and the group comprising high insulin resistance (HIR). Results. Seventy GDM cases and 149 NGT cases were identified. By using receiver operating characteristic curve analysis, the HOMA-IR cut-off value was determined to be 1.41. Twenty-five GDM cases (36%) were classified as LIR and forty-five GDM cases (64%) were classified as HIR. The background including indications for having 75gOGTT and the gestational age having 75gOGTT did not differ between groups. The BMI of the LIR group was significantly lower than that of the HIR group (20.9±2.8 vs. 24.4 ± 5.5, p<0.01), and the HOMA-β of the LIR group was significantly lower than that of the HIR group (95.5±30.3 vs. 146.0±70.1, p<0.01). A positive linear correlation was found between BMI and HOMA-β in cases of GDM (r=0.27, p=0.02). Conclusion. Leanness with impaired insulin secretion is deeply involved in Japanese gestational diabetes mellitus.